A Layered‐Nanospace‐Confinement Strategy for the Synthesis of Two‐Dimensional Porous Carbon Nanosheets for High‐Rate Performance Supercapacitors. Issue 7 (10th December 2014) - Fan, Xiaoming; Yu, Chang; Yang, Juan; Ling, Zheng; Hu, Chao; Zhang, Mengdi; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> A general approach is developed for the synthesis of 2D porous carbon nanosheets (PCNS) from bio‐sources derived carbon precursors (gelatin) by an integrated procedure of intercalation, pyrolysis, and activation. Montmorillonite with layered nanospace is used as a nanotemplate or nanoreactor to confine and modulate the transformation of gelatin, further leading to the formation of 2D nanosheet‐shaped carbon materials. The as‐made 2D PCNS exhibits a significantly improved rate performance, with a high specific capacitance of 246 F g−1 and capacitance retention of 82% at 100 A g−1, being nearly twice that of microsized activated carbon particulates directly from gelatin (131 F g−1, 44%). The shortened ion transport distance in the nanoscaled dimension and modulated porous structure is responsible for such an enhanced superior rate capability. More importantly, the present strategy can be extended to other bio‐sources to create 2D PCNS as electrode materials with high‐rate performance. This will also provide a potential strategy for configuring 2D nanostructured carbon electrode materials with a short ion transport distance for supercapacitors and other carbon‐related energy storage and conversion devices.